Non-coding and intergenic genetic variants of human arylamine N-acetyltransferase 2 (NAT2) gene are associated with differential plasma lipid and cholesterol levels and cardiometabolic disorders - Hong, Kyung U.; Walls, Kennedy M.; Hein, David W. (Frontiers in Pharmacology, 2023)
Arylamine N-acetyltransferase 2 (NAT2) is a phase II metabolic enzyme, best known for metabolism of aromatic amines and hydrazines. Genetic variants occurring in the NAT2 coding region have been well-defined and are known to affect the enzyme activity or protein stability. Individuals can be categorized into rapid, intermediate, and slow acetylator phenotypes that significantly alter their ability to metabolize arylamines, including drugs (e.g., isoniazid) and carcinogens (e.g., 4-aminobiphenyl). However, functional studies on non-coding or intergenic variants of NAT2 are lacking. Multiple, independent genome wide association studies (GWAS) have reported that non-coding or intergenic variants of NAT2 are associated with elevated plasma lipid and cholesterol levels, as well as cardiometabolic disorders, suggesting a novel cellular role of NAT2 in lipid and cholesterol homeostasis. The current review highlights and summarizes GWAS reports that are relevant to this association. We also present a new finding that seven, non-coding, intergenic NAT2 variants (i.e., rs4921913, rs4921914, rs4921915, rs146812806, rs35246381, rs35570672, and rs1495741), which have been associated with plasma lipid and cholesterol levels, are in linkage disequilibrium with one another, and thus form a novel haplotype. The dyslipidemia risk alleles of non-coding NAT2 variants are associated with rapid NAT2 acetylator phenotype, suggesting that differential systemic NAT2 activity might be a risk factor for developing dyslipidemia. The current review also discusses the findings of recent reports that are supportive of the role of NAT2 in lipid or cholesterol synthesis and transport. In summary, we review data suggesting that human NAT2 is a novel genetic factor that influences plasma lipid and cholesterol levels and alters the risk of cardiometabolic disorders. The proposed novel role of NAT2 merits further investigations.